2021
DOI: 10.1007/s00406-021-01358-5
|View full text |Cite
|
Sign up to set email alerts
|

Detailing the effects of polypharmacy in psychiatry: longitudinal study of 320 patients hospitalized for depression or schizophrenia

Abstract: Current treatment standards in psychiatry are oriented towards polypharmacy, that is, patients receive combinations of several antidepressants, antipsychotics, mood stabilizers, anxiolytics, hypnotics, antihistamines, and anticholinergics, along with other somatic treatments. In tandem with the beneficial effects of psychopharmacological drug treatment, patients experience significant adverse reactions which appear to have become more frequent and more severe with the rise of ubiquitous polypharmacy. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…However, the extent of this presumed specificity is severely limited, because many drugs, especially APDs, act on a variety of different receptor systems (e.g., dopamine, histamine, serotonin, and acetylcholine) (Siafis et al 2018 ). Further overshadowing the potential benefits of this technique is the simple fact that polypharmacy is not considered more efficacious than monotherapy (Stassen et al 2021 ) and is also is a well-established risk factor for ADRs (Zopf et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the extent of this presumed specificity is severely limited, because many drugs, especially APDs, act on a variety of different receptor systems (e.g., dopamine, histamine, serotonin, and acetylcholine) (Siafis et al 2018 ). Further overshadowing the potential benefits of this technique is the simple fact that polypharmacy is not considered more efficacious than monotherapy (Stassen et al 2021 ) and is also is a well-established risk factor for ADRs (Zopf et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data from patients and controls from five of our previous studies were (1) pooled, (2) coded in a standardized way, and (3) analyzed together. The study details can be found elsewhere [13][14][15][16][17][18]. Totally 1,698 subjects were genotyped for 100 genes 4 and 549 specifically selected SNPs at a missing data rate < 5% (96 autosomal genes; 1,431 psychiatric patients; 267 healthy controls, of which 141 (52.8%) were unaffected 1st degree relatives of the patients).…”
Section: Methods: Data Materialsmentioning
confidence: 99%
“…Among the exogenous factors, lifestyle, diet, consumption behavior, and physical activity play a prominent role. Inflammation is another major exogenous constituent explaining some 15-25% of the observed phenotypic variance [3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important aspect of pharmacogenetic research is the possibility of anticipating the consequences of concomitantly administering multiple drugs, which is far from being an isolated phenomenon in patients with SPDs. Polypharmacy was found in 85% of the hospitalized patients enrolled in a study ( N = 320 participants diagnosed with schizophrenia spectrum disorders (SSD) or depressive disorders ( 12 ). On average, these patients received 4.5 ± 2.7 medications, out of which 3.3 ± 1.8 were psychotropics ( 12 ).…”
Section: Introductionmentioning
confidence: 99%